Authentic leadership, perceived organizational support, and psychological capital: Implications for job performance in the education sector - Sarwar, Uzma; Aamir, Muhammad; Bichao, Yu; Chen, Zhongwen (Frontiers in Psychology, 2023)
The present study sifts the indirect role of psychological capital in linking authentic leadership and job performance. Furthermore, this study investigates the interplay of authentic leadership and perceived organizational support (POS) in psychological capital. We tested these assumptions through macro PROCESS with two sources of data collected from 350 employees and their respective colleagues working in education sector organizations in China. The study findings established that authentic leadership positively influences employee performance directly and indirectly through psychological capital. POS ‎moderates the effects of authentic leadership on psychological capital such that this relationship gets more pronounced in individuals with high ‎levels of POS. All organizations in the education sector can benefit from the current study's practical application. We recommend that firms create and implement these training programs to improve job performance since authentic leadership is favorably correlated with job performance. The organization should pick executives with a vision to encourage e-job performance. In order to promote this behavior, firms can also hold management training seminars, conferences, and programs. Making performance a clear necessity within job criteria will encourage it among personnel. To achieve great results, top management and leadership must inform the workforce about the importance of authentic behavior in the workplace.